Factors Associated With Acute Respiratory Infections Among Children Aged 6–10 In The Working Area of Putri Ayu in 2025 - Alvin Maha Syagar; Fajrina Hidayati; Herwansyah Herwansyah; Oka Lesmana; Ashar Nuzulul Putra (International Journal of Health Engineering and Technology, 2026)
Acute Respiratory Infections (ARI) remain a common health problem in the working area of Putri Ayu Public Health Center. Behavioral factors and household environmental conditions are suspected to contribute to the increased risk of ARI. To determine the factors associated with the incidence of ARI among children aged 6–10 years in the working area of Putri Ayu Public Health Center in 2025. This study used a cross-sectional design with sampling conducted among community members who met the inclusion criteria. Data were analyzed using the Chi-Square test and Prevalence Ratio (PR) calculations. The findings showed significant associations between handwashing with soap (p-value = 0,049), smoking habits (p-value = 0,000), occupancy density (p-value = 0,033), and household ventilation (p-value = 0,044) with ARI incidence. Meanwhile, temperature (p-value = 1,000), humidity (p-value = 0,625), and lighting (p-value = 0,400) showed no significant associations. Smoking habits had a PR of 6.696, indicating that children living with smoking family members have nearly seven times higher risk of developing ARI. Behavioral factors such as handwashing and smoking habits, as well as environmental factors such as ventilation and occupancy density, are associated with ARI incidence. Promotive and preventive efforts are needed, particularly reducing indoor smoking and improving household ventilation.